2012
DOI: 10.3109/00016357.2012.715201
|View full text |Cite
|
Sign up to set email alerts
|

Influence of prophylaxis paste treatment on the abrasive wear of surface sealants

Abstract: OBJECTIVE: To investigate the abrasive wear of surface sealants (SealProtect and K-0184 (experimental sealant)) and the influence of pre-treatment with mineral deposit forming prophylaxis pastes (NUPRO Sensodyne and NUPRO) on this wear. METHODS: One hundred and eight bovine dentine samples were randomly allocated to nine groups (1-9). Pre-treatment (10 s): groups 1-3: untreated, groups 4-6: NUPRO, groups 7-9: NUPRO Sensodyne. Sealing: groups 1, 4 and 7: unsealed, groups 2, 5 and 8: SealProtect, groups 3, 6 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…On the other hand, in those studies that showed a higher cytotoxicity after shorter light-curing time, restorative resin composites [14] or resin luting cements [13] with a thickness of the samples of 2 mm and 1 mm were tested, respectively. In contrast, the layer thickness of the sealants tested in the present study commonly amounted to between 22 μm [39] to 40 μm [40]. We assume that due to this much lower thickness of the sealant’s layer, shortening of the light-curing duration has a lower influence on the cytotoxicity, as the curing light can easily reach the bottom side of the samples (sealant layer).…”
Section: Discussionmentioning
confidence: 90%
“…On the other hand, in those studies that showed a higher cytotoxicity after shorter light-curing time, restorative resin composites [14] or resin luting cements [13] with a thickness of the samples of 2 mm and 1 mm were tested, respectively. In contrast, the layer thickness of the sealants tested in the present study commonly amounted to between 22 μm [39] to 40 μm [40]. We assume that due to this much lower thickness of the sealant’s layer, shortening of the light-curing duration has a lower influence on the cytotoxicity, as the curing light can easily reach the bottom side of the samples (sealant layer).…”
Section: Discussionmentioning
confidence: 90%